POLA PENDIDIKAN AGAMA KRISTEN DALAM KELUARGA PETANI DI DESA O’BAKI KECAMATAN KOKBAUN KABUPATEN TIMOR TENGAH SELATAN - Nofriana Baun; Sumeriani Tsu; Amelia Wila (Jurnal Dedikasi Pendidikan, 2023)
The farmer family in the village O'baki, TTS Regency, is a family that carries out its role in educating children through several patterns, namely, habituation patterns, advice, guiding, participation, maintenance, example, and discipline. The purpose of this research is to find out the pattern of Christian religious education in farming families. The theory in this study is the pattern of Christian religious education and the farmer's family. The method used is a type of descriptive qualitative research. Primary data sources totaled 12 people, consisting of the village head, the PKK head, and 10 parents in O'Baki village. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study show that the pattern of Christian religious education for farming families in the village of O,Baki greatly influences the lives of children in the future. Children need to receive full assistance toward maturity mentally, physically, and spiritually.